A Systematic Review of High-Intensity Interval Training Protocols and Their Effects in BMI And Metabolic Biomarkers in Obese Adolescents: A Focus on Randomized Controlled Trials - Tanti Ajoekesoema; Carissa Putri Crisdayani; Elita Syaravina; Banundari Rachmawati; Hardhono Susanto; Angela B. M. Tulaar (Diponegoro International Medical Journal, 2025)
Background: Adolescent obesity is a growing public health concern, associated with chronic diseases such as cardiovascular disease, type 2 diabetes, and non-alcoholic fatty liver disease. High-Intensity Interval Training (HIIT) has been identified as a potential intervention to improve weight management and metabolic health in this population.Objective: To evaluate the impact of HIIT, alone or in combination with dietary advice, on weight management and metabolic health indicators, including Body Mass Index (BMI), fasting serum glucose levels, and metabolic biomarkers in adolescents with overweight or obesity.Methods: This systematic review included randomized controlled trials (RCTs) focusing on adolescents aged 16 to 19 with a BMI of 23 kg/m² or above. Studies were selected based on predefined criteria, excluding cross-over trials and quasi-randomized studies. Primary outcomes were changes in BMI, fasting serum glucose, and metabolic biomarkers. Secondary outcomes included measures of insulin resistance. The GRADE methodology was used to appraise the certainty of evidence.Results: Five RCTs were included, demonstrating that HIIT, especially when combined with dietary advice, significantly improves insulin sensitivity, reduces waist circumference, and enhances cardiometabolic health. The interventions varied in duration and intensity but consistently showed positive outcomes in physical fitness, metabolic biomarkers, and body composition.Conclusion: HIIT, particularly when integrated with dietary advice, offers a promising strategy for managing obesity and improving metabolic health among adolescents. This review supports the adoption of multidisciplinary approaches in clinical practice, aiming to enhance the overall health outcomes of adolescents with overweight or obesity.